1979
DOI: 10.1007/bf02441178
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl content of solution-precipitated calcium phosphates

Abstract: A method is described for determination of the titratable hydroxide ion in calcium phosphate precipitates. The procedure requires accurate analysis of the other titratable species in the crystal lattice but is unaffected by the presence of other lattice constituents or impurities. The method was applied to precipitates that had been previously analyzed by solution thermodynamic techniques, and the results were consistent with the earlier observations. The hydroxide content of the precipitates increased with cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The amounts of P2074-formed in our work and Berry's are in good agreement with the amounts predicted from the formula Cal0 xHx(PO4)6(OH)2-x [1], supporting the idea that Ca-deficient apatites are also hydroxyl deficient as has been suggested by others [1,7]. Indeed, recent titration experiments [19] showed that precipitated Ca-deficient HA does contain OH deficiencies. A alp nuclear magnetic resonance study of Ca-deficient apatites, using magic-angle sample spinning, was recently carried out [20].…”
Section: Discussionsupporting
confidence: 92%
“…The amounts of P2074-formed in our work and Berry's are in good agreement with the amounts predicted from the formula Cal0 xHx(PO4)6(OH)2-x [1], supporting the idea that Ca-deficient apatites are also hydroxyl deficient as has been suggested by others [1,7]. Indeed, recent titration experiments [19] showed that precipitated Ca-deficient HA does contain OH deficiencies. A alp nuclear magnetic resonance study of Ca-deficient apatites, using magic-angle sample spinning, was recently carried out [20].…”
Section: Discussionsupporting
confidence: 92%
“…An example is the established correlation [4,13] between the mean pIAP of CAP and CAP crystallinity (crystallite microstrain) where crystallinity is a (mean) bulk property. Another example is that based on the outcomes of the present research: the MES of CAPs of low crystallinity may be governed by a surface complex with the calcium/hydroxide deficient hydroxyapatite stoichiometry-which is consistent with literature that poorly crystallized hydroxyapatite has a propensity toward having a bulk stoichiometry of Ca 9 (HPO 4 )(PO 4 ) 5 OH [29][30][31][32][33][34][35][36][37][38].…”
Section: A Further Aspect Of the Nature Of The Surface Complexsupporting
confidence: 63%
“…At pH 7.4, scribe the maturation of these ACPs to form about 10% of the phosphate was HPO~ions as brushite. The usefulness of Fourier transform injudged from the form of the solubility product frared spectroscopy to distinguish between the controlling precipitation [2], and at higher pH the acidic and basic ACPs is demonstrated and we composition became more complex as OH-ions show that the short range structure around the may have been incorporated [3]. Likewise, in precalcium ions in these acidic ACPs is similar to that cipitations from solutions containing magnesium in the basic ACP.…”
mentioning
confidence: 79%
“…The specare in agreement in demonstrating that an appretrometer used was a Nicolet 20 SX B model ciable fraction of the phosphate groups are prooperating at a resolution of 2 cm' over the range tonated. Titration methods such as the oxalate 4000-250 cm method or the acid/base titration of Meyer [3] or To erthance features of the infrared spectra, the charge balance calculation do not determine Fourier self-deconvolution was employed [26], as the separate H + and OH -components but only implemented in the FSD software package from their difference. The infrared spectroscopic evithe instrument manufacturer.…”
Section: X-ray Powder Diffractionmentioning
confidence: 99%